Clinical and Radiological Evaluation of Congenital Clubfoot (CTEV) Treated with Ponseti Technique and Its Outcomes - HKS Chawla; BS Brar; Ashish Garg; Nitish Kohli (GMC Patiala Journal of Research and Medical Education, 2019)
Background - Congenital Clubfoot (CTEV) occurs in approximately one in 1000 live births and is one of the most congenital birth defects. It is usually defined as a fixation of the foot in adduction, equinus, cavus and varus. The Ponseti method is at present a well-established method of treatment of idiopathic clubfoot deformities. The purpose of this study was to evaluate the results of serial casting with Ponseti method in orthopaedic clinics of Government Medical College and Rajindra Hospital Patiala on the basis of Pirani's Scoring and Radiological findings before and at the end of treatment. Materials & Methods – A total of 30 patients were enrolled in the study and were treated with Ponseti's casting after grading the severity of deformity clinically by Pirani's scoring and Radiologically by calculating the Talo-first metatarsal angle in AP view and Talo-Calcaneal angle in AP and stress dorsiflexion lateral views. Same clinical and radiological parameters were again assessed at the end of treatment before commencement of Foot abduction orthosis. Results – The average number of casts applied before full correction was was 5.56 ranging between 5 to 8. Average duration of treatment was about 6.65 weeks before the patient was put on FAO (foot abduction orthosis). Pirani score significantly improved from an average of 5.50 (range 4-6) on presentation to 0.24 (range 0-2) after correction. Conclusion– Ponseti's method of manipulation and plaster Casting corrects all 4 deformities associated with patients of congenital idiopathic clubfoot which is evident by statistically significant improvements clinically as measured by Pirani severity score and radiologically by Talo-calcaneal and Talo-first metatarsal angle and is associated with lower rates of complications.